Kebijakan Peningkatan Kualitas Perguruan Tinggi Keagamaan Islam Menuju World Class University - Qoyyimun Nafal; Mujamil Qomar; Abd. Aziz (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Islamic religious universities play an important role in spreading religious values, promoting a deep understanding of Islam, and contributing to the intellectual development of Muslims globally. This research aims to analyze the policies needed to improve the quality of Islamic religious universities towards world-class university status. This research uses a library method in which researchers collect various literature for analysis. Research findings show that there are challenges for Islamic religious universities as they move towards becoming world-class universities. This research provides an in-depth view of concrete steps that can be taken by educational institutions and governments to encourage the growth and development of Islamic religious universities globally.